Blending and Spending: Financial Influences Impacting Childfree Stepmothers’ Relationship Satisfaction - Diane W. Darling; Lauren Mizock; Allen E. Cornelius; Ashley B. LeBaron-Black; Amy Taylor (Journal of Financial Therapy, 2024)
There exists a need to better understand how monetary factors impact the partnerships of childfree stepmothers in blended families. The present study examines the correlation of couples’ shared financial values and congruence in financial management behaviors with relationship satisfaction among these stepmothers. Participants included 104 childfree stepmothers in blended families. Findings indicated that perceived shared financial values positively predicted relationship satisfaction. In addition, while financial behavior congruence between stepmothers and their partners did predict relationship satisfaction, it did so through a weaker inverse association. Contrary to expectations, financial behavior congruence did not mediate the association between shared financial values and relationship satisfaction. These results reflect the complex role of financial factors in the well-being of childfree stepmothers within blended families and the need for nuanced psychological and financial support tailored to this oft-overlooked group of women.
Keywords: stepmother; relationship satisfaction; financial behaviors; financial values; blended families